Study on Mode I fatigue behaviour of Nylon 6, 6 nanoreinforced CFRP laminates. (15th March 2017) - Brugo, T.; Minak, G.; Zucchelli, A.; Yan, X.T.; Belcari, J.; Saghafi, H.; Palazzetti, R.
Abstract: The benefits of interleaving polymeric electrospun nanofibers in between laminae of composite structure have been widely demonstrated in the past several years. Among the work that still has to be done, this paper aims to study delamination propagation of virgin and nanomodified specimens under Mode I fatigue loading. A 40-micron thick layer of Nylon 6, 6 nanofibers have been produced and interleaved in carbon fiber-epoxy resin composite laminates; static and dynamic double cantilever tests have been performed to determine delamination growth onset and crack propagation rate vs. maximum energy release rate respectively. Nanomodified specimens exhibited improved delamination resistance during both the tests: delamination toughness increased 130% and cracks propagated 36–27 times slower than virgin interfaces. The benefits of the nanointerleave and its working mechanism have been explained using micrographs and SEM images, which revealed a double-stage reinforce mechanism.